Molecular imaging for neuroendocrine tumours: This article was corrected and republished online on April 3, 2019. Please see Erratum (Swiss Med Wkly. 2019;149:w20076) (Swiss Medical Weekly, 2019)
Molecular imaging has found numerous applications in oncology as many tumours express or activate tumour specific target molecules or pathways. This relatively new imaging technique results in a better localisation of tumours and improved tumour staging, especially in the setting of hybrid imaging that is in combination with morphological imaging such as computed tomography. In well differentiated neuroendocrine tumours, somatostatin receptor imaging, as one of the first examples of receptor targeted imaging in humans, plays an important role in the diagnostic work-up of these patients. In poorly differentiated neuroendocrine tumours or medullary thyroid carcinoma, 18F-fluorodeoxyglucose PET/CT and dihydroxyphenylalanine PET/CT play an important role due to the limitations of the somatostatin receptor imaging in these tumour entities. These limitations prompted the development of innovations such as radiolabelled somatostatin receptor antagonists for imaging all types of NET and glucagon-like peptide-1 receptor agonists for the imaging of insulinomas. The current review summarises the actual state of knowledge in the field.